Antibacterial and biological properties of biofunctionalized nanocomposites on titanium for implant application. (August 2016) - Li, Peiyuan; Tong, Zhangfa; Huo, Lini; Yang, Fang; Su, Wei
Titanium implants possessing excellent antibacterial activity are highly desirable for the prevention of implant-associated infections. In this study, we demonstrate a simple one-step, water-based procedure for the fabrication of biofunctionalized nanocomposites on titanium for implant application. The formation of biofunctionalized silver nanoparticles with varied biomolecule templates is confirmed by Fourier-transform infrared spectroscopic, contact angle, field-emission scanning electron microscopy, and inductively coupled plasma atomic emission spectrometry analysis. Antibacterial properties of the specimens were determined by challenging them against Staphylococcus aureus . The Ag-incorporated titanium shows excellent antibacterial ability against planktonic bacteria in the suspension and ability to prevent bacterial adhesion. The specimens with optimized biomolecule/silver ratio promote osteoblast differentiation. These biofunctionalized silver nanoparticles-doped titanium specimens, with improved antibacterial activity while maintaining healthy osteoblast cellular activity, have promising application in orthopedics, dentistry, and other biomedical devices.